2014
DOI: 10.1007/s00277-014-2256-0
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal and nodal diffuse large B cell lymphoma of the head and neck: two different entities?

Abstract: This study analyzes patients with head and neck diffuse large B cell lymphoma (HN-DLBCL), focusing on the differences in the biological characteristics and prognosis of lymphomas of nodal and extranodal origin. We have included 72 patients with stage I-II HN-DLBCL who had updated survival information and diagnostic paraffin-embedded tissue blocks available for review. Non-germinal center phenotype (73.7 vs. 32.4 %, P = 0.001) and high level of Bcl-2 expression (78.9 vs. 52.9 %, P = 0.025) were more frequent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Reasons for the inferior outcome of patients with extranodal involvement are largely unknown, but MYC with or without either BCL2 or BCL6 (double‐hit) rearrangements are more common among patients with extranodal disease . In addition, the activated B‐cell phenotype may be more common in DLBCL involving extranodal sites . Double hit and cell of origin were not routinely examined in our study cohort, but their presence may explain the more aggressive clinical course seen in patients with extensive extranodal disease.…”
Section: Discussionmentioning
confidence: 98%
“…Reasons for the inferior outcome of patients with extranodal involvement are largely unknown, but MYC with or without either BCL2 or BCL6 (double‐hit) rearrangements are more common among patients with extranodal disease . In addition, the activated B‐cell phenotype may be more common in DLBCL involving extranodal sites . Double hit and cell of origin were not routinely examined in our study cohort, but their presence may explain the more aggressive clinical course seen in patients with extensive extranodal disease.…”
Section: Discussionmentioning
confidence: 98%
“…The vast majority of these are NHL, approximately 85%, and of the DLBCL subtype, approximately 80%, as in our patient [4]. Two-thirds of these are confined to lymph nodes and one-third are so-called extranodal lymphomas [7]. HL is exceedingly rare outside of lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
“…For stage III and IV disease, survival is closer to 50% at 5 years [3]. Sanchez et al performed a retrospective review of patients with DLBCL of the head and neck and found that extranodal DLBCL may have an overall better response to treatment than nodal DLBCL [7].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[18][19][20] In an analysis of immunochemotherapy-treated HN DLBCL patients, including nine SNT cases (including also larynx tumors), 68% of the extranodal HN DLBCL patients had GCB immunophenotype, but SNT DLBCL was not studied separately, 21 the COO did not have an impact on survival. 21 In a Japanese study on 29 SNT DLBCL patients treated between 2002 and 2013, 82% of the patients had non-GCB immunophenotype, which correlated with inferior survival. 22 BCL2 expression has been observed in 55% of the Waldeyer's ring DLBCL patients and found to associate with adverse survival in the pre-R era, the effect, however, overcome by COO distinction.…”
mentioning
confidence: 99%